Internal democracy in the ANC or, did the Polokwane Revolt challenge Michels' "Iron law of oligarchy?" - Lukhele, Sibusiso (My University, 2011)
Can political parties be democratic? This is one of the larger theoretical questions that have to be asked. The ANC has been the governing party for the last fifteen years in a democratic South Africa. For the last fifteen years the ANC has ruled with a majority, reaching the symbolic two-thirds majority in the 2004 elections, which it subsequently narrowly lost in the 2009 elections. Internal party democracy is particularly important in states that are dominated by one party, where there fewer effective ways of keeping the government accountable. The ANC has exhibited worrying trends over the last fifteen years towards suppressing dissent in the party, despite its constitution stating that members can raise their grievances within party structures. In a state dominated by a single party, as in South Africa, internal battles within the ruling party play out in the public realm. We have seen public institutions like the NPA and the SABC being used by various factions within the ANC to settle ‘political scores’ and more importantly to stop challenges posed to the current leaders of one faction. The manipulation of these institutions by elected leaders does not bode well for the country. Internal democracy issues have thus become issues for the entire country
Internal democracy in the ANC or, did the Polokwane Revolt challenge Mixchels' "Iron law of oligrachy?"'
Internal democracy in the ANC or, did the Polokwane Revolt challenge Michels' "Iron law of oligarchy?"